Directory Of State Publications Listing Crushed Stone And Sand And Gravel Producers 1994 ? Introduction (The National Institute for Occupational Safety and Health (NIOSH), 1994)
A significant amount of information regarding the crushed stone and sand and gravel industries in each State is available from State agencies and State trade associations. These organizations continuously monitor the State mineral industries and are therefore an important source of detailed information at the local level. This third edition of the directory was prepared to provide a listing of government agencies and trade associations that can assist the users interested in obtaining detailed listings of crushed stone and sand and gravel producers, in addition to the information published by the U.S. Bureau of Mines.